PENERAPAN METODE BERMAIN PERAN UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPS POKOK BAHASAN JENIS‐JENIS USAHA EKONOMI DI SDN NGADILUWIH 02 KEDIRI - zulfa nairurohmah; Chumi Zahroul (Universitas Muhammadiyah Surabaya, 2016)
The Social Scients Subject learning activities in SDN Ngadiluwih 02 Kediri yet using a variety of learning methods. According to the observation of prasiklus known that the activity and student learning outcomes have not been included in both criteria. Precentation of student activity in the prasiklus in highly active criteria is12% (3 students), in the active criteria is 16% (4 students), in the quite active criteria is 56% (14 students), in the low active criteria is 16% (4 students). The means of student learning activity in prasiklus is 56% (quite active criteria). Precentation of student learning outcomes in the very good criteria is 24% (6 students), in the good criteria is 24% ( 6 students), in the good enough is 36% (9 students), in the not good is 16% (4 students). The means of student learning outcomes in prasiklus is 68 (good enough criteria).Based on these findings the need for a more varied teaching methods with emphasis on student activity and provide opportunities for students to develop their learning abilities to the fullest. In accordance with these problems, the goal of this research is to improve the activity and student learning outcomes in class V through the application of learning methods Role Playing IPS Highlights Types of economic activities in SDN Ngadiluwih 02 Kediri. This type of research is classroom action research (PTK) are conducted in two cycles. The results obtained in this study indicate that through the implementation of Role Playing method can increase the activity and student learning outcomes. The average activity of students in prasiklus is 56,4% (quite active criteria). In the first cycle increased to 70,8% (active criteria). In the second cycle increased again to 80,96% (highly active criteria). The means score on the student learning outcomes prasiklus is 68 (criteria quite well). In the first cycle increased to 73.2 (good criteria). In the second cycle increased again to 83.18 (very good criteria). Keywords: Role Playing Method, student lerning activity, student learning outcomes, classroom action research.